Curriculum Integration and Scientific Research Training: A Study on the Path to Cultivate Graduate Students’ Academic Norms Cognition and Paper Writing Ability - Zhan, Haiyu (Journal of Research in Vocational Education, 2025)
This article discusses the course “Academic Norms and Graduate Thesis Writing Guidance,” emphasizing the crucial role of adhering to academic standards in the process of thesis writing. It outlines the key aspects of thesis composition, including topic choice, literature review, and research methodologies, while underscoring the necessity to steer clear of non-conforming practices. The course aims to integrate learning with thesis writing, improve academic norms, and encourage innovative thinking within ethical boundaries. Ultimately, it emphasizes the importance of academic innovation and underscores the necessity for students to grasp the orientation of their thesis work, acknowledge academic boundaries, and aspire to achieve success.